The effect of light-emitting diode wavelengths on biomass accumulation of butterhead lettuce - Goh, Eugene Mugen (2014)
Improvement in plant cultivation techniques is of perennial relevance. LED lighting systems have been making headway as a suitable substitute for sunlight. This opens up the possibility to farm in indoor spaces in a multi-leveled fashion. Though LED lighting systems has been around for some time it is still not widely utilized as cost, optimizing information and installation costs are high. However, it is hoped that further research will instill more confidence and viability in the application of LED technology. The primary objective of this project is to verify the effects of LED lighting system wavelengths and Photon Photosynthetic Flux Density (PPFD) intensities have on the biomass accumulation of Butterhead lettuce with existing research results established overseas. The assembly of the set-up was done at the Bottletree Park. Butterhead lettuce saplings were procured from OH! Chin Huat hydroponic farm. LED light, blue (B), white (W), a combination of red and blue (RB) and a combination of red, blue and white (RBW) treatments were used as the four growth conditions in this experiment. LED lamps were the sole source of light energy (absence of sunlight) for this experiment. The measured parameters are percentage growth of plants in terms of weight, number of leaves, fresh weight, dry weight, root mass, leaf width, leaf thickness, chlorophyll level and taste related criteria. It was shown that RB had the healthiest overall growth in terms of biomass accumulation. Specimens under W and RBW had higher biomass accumulation means than B but were not as favorable as RB. Specimens under B treatment performed the worst as it lacked R region wavelengths. It is observed that in terms of root volume, RB is the densest, while RBW and W are similar but less than that of RB, while B is the least dense. It can be deduced that W LED treatment alone is not sufficient for healthy biomass accumulation. For RBW, though both red and blue peaks are present, there was an overall low intensity at R. This shows that the absence of sufficiently high intensity in both B and R regions had obvious detrimental effects on plant biomass accumulation. It was further shown that specimens under a higher PPFD of around 150 µmol/mm2/s had healthier growth than those under lower PPFD. Sensory parameters were the best in RB specimens. Overall, it was found that RB treatment was the most favorable for plant growth as opposed to W, RBW and B.